Pendidikan Agama Islam di Sekolah Muslim Swedia - Maulana, Denih (ANWARUL, 2022)
In the literature on Islamic religious education (IRE), the process of teaching Islam to the younger generation is often referred to as "transmitting Islam". Obviously, there are certain "facts" that are often transmitted from one generation to another, such as the names of prophets, the five pillars of Islam and the words of the Quran. But what meaning and meaning people have and these concepts are not necessarily "transmitted". In this paper, I argue that using the concept of "transmit- ting" raises some problems, such as providing a static view of the Islamic educational process, thus ignoring the contextualization that is an important part of all teaching. Referring to Homi Bhabha, I instead suggest that the concept of translation is more accurate to what Islamic religious education teachers do, because translation includes the idea of interpretation and thus shows the power that teachers have when they make educational choices. The empirical material used comes from fr om fieldwork in Swedish Muslim schools.